2021
DOI: 10.3390/ijms22115437
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Empagliflozin Improves Systolic Heart Function after Myocardial Infarction in Rats: Regulation of MMP9, NHE1, and SERCA2a

Abstract: The effects of the selective sodium-glucose cotransporter 2 (SGLT2) inhibitor empagliflozin in low dose on cardiac function were investigated in normoglycemic rats. Cardiac parameters were measured by intracardiac catheterization 30 min after intravenous application of empagliflozin to healthy animals. Empagliflozin increased the ventricular systolic pressure, mean pressure, and the max dP/dt (p < 0.05). Similarly, treatment with empagliflozin (1 mg/kg, p.o.) for one week increased the cardiac output, strok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 50 publications
(86 reference statements)
2
18
0
Order By: Relevance
“…In H9C2 cardiac cells, EMPA (1 μM) in the presence of albumin decreased the matrix metalloprotease (MMP)2 and MMP9 activity induced by IL-1 alpha and prevented apoptosis [ 35 ]. CANA (3 μM) in the presence of albumin was able to reduce ROS production in human right and left atrial tissue and cultured cells through inhibition of a SGLT1/AMPK/Rac1/NADPH oxidase pathway, whereas EMPA was without any effect [ 36 ].…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…In H9C2 cardiac cells, EMPA (1 μM) in the presence of albumin decreased the matrix metalloprotease (MMP)2 and MMP9 activity induced by IL-1 alpha and prevented apoptosis [ 35 ]. CANA (3 μM) in the presence of albumin was able to reduce ROS production in human right and left atrial tissue and cultured cells through inhibition of a SGLT1/AMPK/Rac1/NADPH oxidase pathway, whereas EMPA was without any effect [ 36 ].…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…MMP9, also known as gelatinase B, can degrade elastin and collagen and is involved in inflammatory responses, and is one of the most extensively studied MMPs in cardiovascular and renal research ( 81 , 82 ). Low-dose empagliflozin can improve systolic heart function after MI in rats by regulating MMP9 ( 83 ). Luseogliflozin regulates the expression of multiple mRNA, including MMP9, and inhibits the progression of atherosclerosis in diabetic APOE-deficient mice ( 84 ).…”
Section: Discussionmentioning
confidence: 99%
“…MMP9 also plays an important role in disease processes, including in embryonic development, reproduction tissue remodeling, arthritis, and metastasis (33). Goerg et al (34) reported that downregulation of MMP9 protein expression in (35). PELI1 can facilitate the activity of ubiquitin protein ligase, and it participates in negative regulation of necroptotic procedure, protein polyubiquitination, and reaction to LPS (36).…”
Section: Discussionmentioning
confidence: 99%
“…MMP9 also plays an important role in disease processes, including in embryonic development, reproduction tissue remodeling, arthritis, and metastasis ( 33 ). Goerg et al ( 34 ) reported that downregulation of MMP9 protein expression in the heart by empagliflozin could improve systolic heart function after myocardial infarction (MI) in rats. A study by Mujumdar et al demonstrated that the activation of MMP9 decreased cardiac tensile strength ( 35 ).…”
Section: Discussionmentioning
confidence: 99%